The Effect of Railway Travel on Urban Spatial Structure - Martijn I. Dröes; Piet Rietveld (Tinbergen Institute, 2014)
We examine the effect of railway travel on urban spatial structure in a polycentric urban land use model. We focus on the role of access to the railway network. We find that if the number of train stations is limited, the degree of urbanization is higher around train stations, but the effect of railway travel on road congestion is small. By contrast, if train stations are omnipresent there is little effect on urban spatial structure, but a considerable decrease in congestion. With regard to the supply of train stations, these findings suggest that there is an important policy trade-off between congestion and urbanization.
Keywords: C68; D58; R13; R14; R4; 330; general equilibrium; public transport; land use model; railway; sorting